Customer Satısfactıon (Publıc Satısfactıon) on Servıces in Admınıstratıve Vıllage Offıce - Muhartini Salim; Syamsul Bachri; Muhammad Rahman Febliansa (APMBA (Asia Pacific Management and Business Application), 2018)
It is widely acknowledged that employees in public sector are responsible towards the community or its customers, in order to fulfill the public satisfaction. During reformation era in Indonesia, public sector services also one of the domain that the government need to pay attention on. Therefore this study aimed at determine some factors such as tangible, reliability, responsiveness, empathy, and assurance that individually influence on customer satisfaction. Respondents were 200 visitors of one of the largest public health provider in one of the growing region in south of Indonesia, Bengkulu municipality. The statistics analysis used in this research was Structural Equation Model operated through AMOS 21 program. The results showed that tangible, reliability, responsiveness, empathy, and assurance individually influence customer satisfaction.